Framework For Merging Object-Oriented Formal Specifications - Taibi , Fathi (2010)
Software development activities are highly collaborative since they involve several people working on different aspects of the same project. Most often, effective collaboration is the key to the success of a software project where development tasks are carried out in a distributed way and the resulting software documents are merged from time to time. Studies have shown that most of the problems with software projects are directly linked to problems with their requirements. Specifying these requirements is a highly complicated and error-prone phase involving several people specifying the requirements of various stakeholders where a shared specification undergoes continuous revisions through collaboration until reaching a version that satisfies the need of all the stakeholders. This raises the need for frameworks aimed at merging specifications in order to detect, process, and consolidate these revisions while maintaining consistency.